The Implementation Of Character Education In Indonesian Language Learning For Class Va Students At Sd Inpres Parangrea, Bajeng District, Gowa Regency, South Sulawesi - Muhammad Akhir (Universitas of Muhammadiyah Makassar, 2021)
This study aims to describe the implementation of character education and describe the inhibiting and supporting factors for implementing character education in Indonesian language learning in-class VA students at SD Inpres Parangrea, Bajeng District, Gowa Regency, South Sulawesi. This type of research is qualitative research. The results showed that the character values obtained from the students were religious, tolerant, disciplined, hard-working, independent, creative, curious, fond of reading, friendly/communicative, and responsible. With the implementation of character education in Indonesian language learning in-class VA students at SD Inpres Parangrea, Bajeng District, Gowa Regency, South Sulawesi, it can be carried out well and generally, taking actions such as 1). Learning planning, 2). Implementation of learning, 3). Learning evaluation. The inhibiting and supporting factors for the implementation of character education in Indonesian language learning for class VA students at SD Inpres Parangrea, Bajeng District, Gowa Regency, South Sulawesi. In comparison, the supporting factors of the implementation of character education in learning Indonesian in-class VA students at SDI Parangrea are 1). Teacher, 2). Character building at school.Penelitian ini bertujuan untuk mendeskripsikan implementasi pendidikan karakter dan mendeskripsikan faktor penghambat dan pendukung implementasi pendidikan karakter dalam pembelajaran bahasa Indonesia pada peserta didik kelas VA di SD Inpres Parangrea Kecamatan Bajeng Kabupaten Gowa Sulawesi Selatan. Jenis penelitian ini adalah penelitian kualitatif. Hasil penelitian menunjukkan bahwa nilai karakter yang diperoleh dari peserta didik yaitu religius, toleransi, disiplin, kerja keras, mandiri, kreatif, rasa ingin tahu, gemar membaca, bersahabat/komunikatif, dan tanggung jawab. Dengan adanya implementasi pendidikan karakter dalam pembelajaran bahasa Indonesia pada peserta didik kelas VA di SD Inpres Parangrea Kecamatan Bajeng Kabupaten Gowa Sulawesi Selatan dapat terlaksana dengan baik dan secara garis besar yaitu dengan adanya tindakan seperti: 1). Perencanaan pembelajaran, 2). Pelaksanaan pembelajaran, 3). Evaluasi pembelajaran. Faktor penghambat dan pendukung implementasi pendidikan karakter dalam pembelajaran bahasa Indonesia pada peserta didik kelas VA di SD Inpres Parangrea Kecamatan Bajeng Kabupaten Gowa Sulawesi Selatan. Sedangkan faktor pendukung dari implementasi pendidikan karakter dalam pembelajaran bahasa Indonesia pada peserta didik kelas VA di SDI Parangrea adalah 1). Guru, 2). Pembinaan karakter di sekolah.